A structural empirical analysis of retail banking competition: The case of Hungary - József Molnár; Márton Nagy; Csilla Horváth (Magyar Nemzeti Bank, 2006)
In this paper we analyze the degree of competition in the Hungarian household credit and deposit markets. We estimate discrete-choice, multinomial logit deposit service and loan demand functions for each bank and calculate the corresponding price elasticities. Two models of the banking industry are considered: a static, differentiated product Nash-Bertrand oligopoly (as non-collusive benchmark) and a cartel. With estimated marginal costs and observed interest rates we calculate the price-cost margins and compare these to the theoretically implied ones. We find that in our sample period the competition in the Hungarian banking sector is low, i.e. price-cost margins are high.
Keywords: G21; L11; L13; 330; demand; discrete choice; product differentiation; banking; market power; Privatkundengeschäft; Wettbewerb; Diskrete Entscheidung; Schätzung; Ungarn